Immediate placement, immediate loading of single implant in fresh extraction socket - Gaurav Gupta; D K Gupta; Neelja Gupta; Priyanka Gupta; Kuldeep Singh Rana (Wolters Kluwer Medknow Publications, 2019)
Smile is an important factor which enhances our beauty. A well-formed complete smile is the basis for facial esthetics. To bring out a beautiful smile, a full set of dentition is necessary. The replacement of missing teeth with implant-borne restorations has become the treatment of choice these days. According to recent reports, the successful implant placement in fresh extraction socket is made possible by modifying the surface of implants. The present case report highlights on the high survival rate of immediate implant loading placed successfully in fresh extraction socket which was confirmed by implant stability quotient (resonance frequency analysis) to assess implant stability noninvasively.